Soil suction dataset from a lime & cement treated embankment, from 2010 to 2023 - Yasmina Boussafir; Dimitri Mercadier; Christophe Piquet (Data in Brief)
An experimental embankment was built in 2010 in the frame of TerDOUEST Project [1]. Treated silt and clay from the site near Héricourt in France, were used in four sections approximately 50 meters length, and 5 meters high. The first meter at the base of the embankment is buried in the soil, below the ground, to study soil-water table interaction. In this site, a water table is located at approximately 1 to 2 meters depth and is registered with a piezometric probe. The last four meters of Héricourt embankment is above the ground level. The slope of this earth structure is V1:H2. One side of the embankment, has been built with the Low Plastic silt classified A2 according to the French standard NF P11-300 [2], treated for one third with 2% of quick lime, and another third section with 3% of cement (previously CEMII). The last third section was not treated. The other side of the embankment used clay, considered as a Plastic Clay and classified A4 [2]; one third has been treated with 4% of quick lime, another third section, with 2% of quick lime and 3% of cement, and the last third was not treated. In each of the treated sections, sensors were buried at 0.25 - 0.50 and 0.75 m depth in the slope, recording volumetric water content and suction for soil-atmosphere interactions studies. Other sensors recorded the volumetric water content only, in the core of the embankment, its base and the platform [3]. All data are available from 2010 to 2023. A weather station recorded precise meteorological data from 2010 to 2013.The goal of this real size embankment was to evaluate the sustainability of treated soils used in earth structures and to test the re-use of very plastic clay thanks to adapted soil treatment. After more than 10 years old, this structure is stable, even if intrinsec characteristics may evolve [4].